An electrothermal model of memory switching in vertical poly crystalline silicon structures - Mahan, John E., author; Malhotra, Vinod, author; Ellsworth, Daniel L., author; IEEE, publisher (Colorado State University. Libraries, 1988)
A previous publication described an experimental investigation of memory switching in vertical thin-film structures formed in polycrystalline silicon. An electrothermal model of switching in those structures is presented here. The theoretical preswitching temperature, resistivity, and current density distributions within the device were obtained from the solution of the transient two-dimensional heat equation. The results of the computer simulation, obtained for the case where conductivity is dependent on both temperature and electric field, show that current crowding occurs at the center of the device and that thermal runaway develops in a few tens of nanoseconds for voltages above a critical value. A simulated conductive irregularity forces the filament to nucleate away from the center and closer to or at the inhomogeneity. The excellent agreement between the experimental data and the simulation lends support to the idea that the fundamental switching mechanism is thermal in nature.